The effectiveness of a large protected area to conserve a global endemism hotspot may vanish in the face of climate and land-use changes - Wang, Danyang; de Knegt, Henrik J.; Hof, Anouschka R. (Frontiers in Ecology and Evolution, 2022)
Endemic vertebrates are a crucial component of biodiversity, yet face disproportionally high extinction risk as climate and land-use changes drive habitat loss. Large protected areas are therefore deemed necessary to mitigate biodiversity loss. In 2021, China’s Giant Panda National Park (GPNP, 27,134 km2) was established in one of the global endemism hotspots. In this study we ask the question whether this large national park is able to conserve the many threatened endemic vertebrates occurring in the region in the face of climate and land-use changes, in order to assess the long-term effectiveness of the GPNP. We used species distribution modelling techniques to project the distributions of 40 threatened terrestrial (and freshwater) endemic vertebrates under land-use and climate change scenarios SSP2-4.5, SSP3-7.0 and SSP5-8.5 in 2081-2100, and assessed the extent to which their distributions are covered by the GPNP, now and in the future. We found that by 2081-2100, two thirds of the threatened endemic vertebrates are predicted to lose part (15 - 79%, N = 4) of or (nearly) their entire (80 - 100% loss, N = 23) range under all three climate and land-use change scenarios. Consequently, fewer species are predicted to occur in the GPNP than at present. Our findings confirm the high vulnerability of threatened endemic species to climate and land-use changes, despite protected areas. Habitat loss due to climate and land-use changes elevate extinction risk of species in endemism hotspots across the globe. Urgent, widespread and intensified mitigation measures and adaptation measures are required at a landscape scale for effective conservation efforts in the future.